Dorsata si Ilmuwan: Mengungkap Kejadian Sains di Sekitar Kita dengan Media Eksperimen Virtual Berbasis Game Edukasi - Marcelino Budi Prakasya; Nathanael Bisma Narayan; Akhmad Bagus Nuryanto (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
In the era of the 4.0 industrial revolution, learners are required to possess innovative and characteristic skills. However, there are some schools that do not have adequate standards in preparing students to face the era of the 4.0 industrial revolution. This results in a low level of understanding and skills among the students. Moreover, boring teaching methods and materials, along with the ongoing COVID-19 pandemic, are also contributing factors to the low level of understanding and skills. As time goes on, technology is advancing, and it has the potential to pique the interest of students for learning and honing their skills. Therefore, an application has been developed to support the understanding and skills of students. This research aims to: 1) Determine how to improve the quality of students' skills. 2) Identify the necessary features to enhance the effectiveness of students in improving their understanding and skills in the subject of physics. 3) Evaluate the effectiveness of the Dorsata learning media in enhancing the understanding and skills of students. This research was conducted through an experimental method, where the first step involved the examination of content and questions by subject matter experts. Subsequently, a practicality questionnaire was administered to assess the practicality of the media. Following this, the media was reviewed by three media experts. Only then was data collected at KT High School, including an assessment of the initial capabilities of the students through a pre-test, an evaluation of the students' experimental skills, and an assessment of their understanding of the learning media. From this research, it can be concluded that the Dorsata Learning Media can assist students in improving the quality of their skills. The necessary features include a digital laboratory, learning materials, laboratory practice worksheets, demonstration videos, and student comprehension tests. The Dorsata Learning Media is also effective in enhancing the understanding and skills of students.